2019
DOI: 10.1103/physrevb.99.184512
|View full text |Cite
|
Sign up to set email alerts
|

Odd-frequency pairs in chiral symmetric systems: Spectral bulk-boundary correspondence and topological criticality

Abstract: Odd-frequency Cooper pairs with chiral symmetry emerging at the edges of topological superconductors are a useful physical quantity for characterizing the topological properties of these materials. In this work, we show that the odd-frequency Cooper pair amplitudes can be expressed by a winding number extended to a nonzero frequency, which is called a "spectral bulk-boundary correspondence," and can be evaluated from the spectral features of the bulk. The odd-frequency Cooper pair amplitudes are classified int… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 78 publications
5
33
0
Order By: Relevance
“…This is similar to what has been reported in multiband superconductors [46][47][48], double quantum dots [50,51], and double nanowires [35,52]. Moreover, when the system is of finite length, we find that, at the edges, the low-frequency odd-ω components in the topological phase develop larger values than the even-ω terms due to MZMs [3,5,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42], an effect we explicitly associate with the topological bulk invariant through the so-called spectral edge boundary correspondence [66,67].…”
Section: Introductionsupporting
confidence: 89%
See 4 more Smart Citations
“…This is similar to what has been reported in multiband superconductors [46][47][48], double quantum dots [50,51], and double nanowires [35,52]. Moreover, when the system is of finite length, we find that, at the edges, the low-frequency odd-ω components in the topological phase develop larger values than the even-ω terms due to MZMs [3,5,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42], an effect we explicitly associate with the topological bulk invariant through the so-called spectral edge boundary correspondence [66,67].…”
Section: Introductionsupporting
confidence: 89%
“…In the topological phase in finite length systems we showed that the low-frequency odd-frequency amplitudes are enhanced at the edges of the system due to the presence of Majorana zero modes. Furthermore, we demonstrated that the spectral bulk-boundary correspondence reveals the relation between intrasublattice odd-frequency correlations and winding number, thus extending previous studies [66,67] to systems with intrinsic staggering, such as the SC SSH model. Our results highlight odd-frequency pairing as a bulk phenomenon that goes beyond the induced effect in junctions and does not require any external actor, such as interfaces in junctions, but instead, this bulk effect solely relies on the intrinsic staggered nature of the system.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations